Metastable effects on martensitic transformation in SMAs: Part X. An approach to thermodynamic changes induced for the S-shaped cycles in thick wires of NiTi - Torra, Vicenç (2017)
The transformation and retransformation paths realized at constant stress in wires of NiTi SMAs show a horizontal or “flat” behavior in the hysteretic cycle. After sinusoidal cycling at 0.01 Hz (i.e., training) with a maximal strain of 8 %, the thicker wires of NiTi SMAs, with a diameter of 2.46 mm, have the stress–strain cycles with one S-shaped behavior. A “similar” change appears by varying the grain sizes in the samples, i.e., from 80 to 20 nm. Furthermore, the local measurements of temperature suggest that cycling induces changes in the transformation mechanisms associated with the evolution from horizontal to S shape. For instance, the associated energy evolves from localized transformation to homogeneous heat production in S-shaped cycles. Thermodynamic analysis establishes a link between heat capacity and the slopes of the coexistence curve in f–x or in σ–ε via the (∂ε/∂σ)coex. The flat cycles were coherent with the classical latent heat, i.e., dissipation at constant stress. In the S-shaped cycles, the heat during the phase change seems redistributed as heat capacity against progressive stress. Preliminary direct measurements are coherent with the evolution of the (∂ε/∂σ)coex against strain.